Protocatechuic Aldehyde Attenuates Cisplatin-Induced Acute Kidney Injury by Suppressing Nox-Mediated Oxidative Stress and Renal Inflammation - Gao, Li; Wu, Wei-Feng; Dong, Lei; Ren, Gui-Ling; Li, Hai-Di; Yang, Qin; Li, Xiao-Feng; Xu, Tao; Li, Zeng; Wu, Bao-Ming; Ma, Tao-Tao; Huang, Cheng; et al. (Frontiers in Pharmacology, 2016)
Cisplatin is a classic chemotherapeutic agent widely used to treat different types of cancers including ovarian, head and neck, testicular and uterine cervical carcinomas. However, cisplatin induces acute kidney injury by directly triggering an excessive inflammatory response, oxidative stress, and programmed cell death of renal tubular epithelial cells, all of which lead to high mortality rates in patients. In this study, we examined the protective effect of protocatechuic aldehyde (PA) in vitro in cisplatin-treated tubular epithelial cells and in vivo in cisplatin nephropathy. PA is a monomer of Traditional Chinese Medicine isolated from the root of S. miltiorrhiza (Lamiaceae). Results show that PA prevented cisplatin-induced decline of renal function and histological damage, which was confirmed by attenuation of KIM1 in both mRNA and protein levels. Moreover, PA reduced renal inflammation by suppressing oxidative stress and programmed cell death in response to cisplatin, which was further evidenced by in vitro data. Of note, PA suppressed NAPDH oxidases, including Nox2 and Nox4, in a dosage-dependent manner. Moreover, silencing Nox4, but not Nox2, removed the inhibitory effect of PA on cisplatin-induced renal injury, indicating that Nox4 may play a pivotal role in mediating the protective effect of PA in cisplatin-induced acute kidney injury. Collectively, our data indicate that PA blocks cisplatin-induced acute kidney injury by suppressing Nox-mediated oxidative stress and renal inflammation without compromising anti-tumor activity of cisplatin. These findings suggest that PA and its derivatives may serve as potential protective agents for cancer patients receiving cisplatin treatment.